Term induction of labour in nulliparous women: When to draw the line? - Jill M. Mitchell; Patrick Dicker; Grace Madigan; Sarah Nicholson; Suzanne Smyth; Fionnuala M. Breathnach (Elsevier, 2022)
Objective: There exists uncertainty surrounding the most effective and efficient means of inducing labour, particularly in the setting of an unfavourable cervix. This study aims to determine the merit of repeating dinoprostone administration when a single application has failed to render the cervix favourable for amniotomy. Study design: Retrospective analysis of a consecutive cohort of nulliparous women who underwent term induction of labour in a tertiary referral centre in Ireland was conducted over a 12- month period (December 2019 to January 2021). The time-interval from dinoprostone administration to delivery and the incidence of complicated birth, associated with single and sequential dinoprostone dosing, were determined. Comparisons were made using the Chi-square test and logistic regression adjusting for gestational age delivery. Results: 586 nulliparous women underwent term induction of labour during the study period. Administration of a single dose of dinoprostone or amniotomy alone were associated with the greatest prospect of an uncomplicated vaginal birth when compared to sequential dinoprostone dosing. Nonetheless, just one in four nulliparous women undergoing induction of labour experienced an unassisted and uncomplicated vaginal birth. The median [interquartile range] for time interval from induction to delivery or decision for caesarean delivery was 0.4 [0.3-0.6] days in those who underwent amniotomy alone, compared to 1.1 [0.7-1.5] days, 1.8 [1.4-2.2] days and 2.2 [2.0-2.6] days for those with 1, 2 or 3 doses of dinoprostone, respectively (p < 0.001 between all groups; Figure 1) Conclusion: These contemporaneous data indicate that in circumstances where more than a single dose of dinoprostone is required for cervical priming in a nulliparous woman, the incidence of an uncomplicated vaginal delivery decreased from more than half of women to less than one third. Over one third of women who were administered either a single dose of dinoprostone or more than one dose experienced an emergency intrapartum Caesarean delivery or a complicated vaginal birth. These findings are relevant to nulliparous women undergoing induction of labour in the setting of an unfavourable cervix and should be incorporated into shared decision-making consultations, particularly when repeat administration of dinoprostone is being considered.